Microscopic description of induced fission dynamics with nuclear energy density functionals - Prassa, Vaia; Tao, H; Zhao, J.; Li, Z. P.; Nikšić, T.; Vretenar, D. (HNPS Advances in Nuclear Physics, 2020)
Static and dynamic aspects of the fission process are analyzed in a self-consistent framework based on energy density functionals. Multidimensionally constrained mean-field calculations in the collective space determine the potential energy surface of the fissioning nucleus, the scission line, the single-nucleon wave functions, energies, and occupation probabilities. Induced fission dynamics is described using the time-dependent generator coordinate method in the Gaussian overlap approximation. The position of the scission line is analyzed as a function of the strength of the pairing interaction, as well as the effect of static pairing correlations on charge yields and total kinetic energy of fission fragments.